Medicine and maladies : representing affliction in nineteenth-century France - Leroy, Sophie, 1988- (Faux titre, 2018)
Medicine and Maladies explores the aesthetic, medical, and socio-political contexts that informed depictions of illness and disease in nineteenth-century France. Eleven essays by specialists in nineteenth-century French literature and visual culture probe the acts of writing, reading, and viewing corporeal afflictions across the works of medical practitioners, surgeons, pharmacists, novelists, and artists. Tracing scientific discourse in literary narratives and signalling references to fiction in medical texts, the contributions to this interdisciplinary volume invite us to rethink the relationship between the humanities and the medical sciences.